Molecular Genetic Analysis of Somaclonal Lines Genotypes of Silver Birch and Hybrid Birch - A. V. Konstantinov; S. V. Panteleev (Сибирский лесной журнал, 2014)
Enrichment of genetic diversity by means of somaclonal variation can allow selection of individuals with increased adaptability to various unfavorable conditions. Twenty shoot cultures differing in organogenesis and morphological features were selected for two studied clones. Multilocus genetic passports of somaclonal lines were developed according to RAPD analysis. Among the samples derived from clone № 52-84/8 shoot cultures the changes in RAPD-spectra were detected over primers UBC-106 and UBC-254. In the case of clone № 6-161/3 the same changes were detected over primers UBC-268 and UBC-154. UBC-203 primer didn’t show any variation.